“Mecanismos de protección de los derechos del consumidor en el ordenamiento jurídico Ecuatoriano” - Edwin Andrés, Llamuca Díaz (2020)
The consumer law, after a generational evolution and an eminent change of paradigms, have been adopted in different legal bodies in our regulations, which are intended to protect the rights of consumers of goods and services, under this background, the work entitled: "MECHANISMS FOR THE PROTECTION OF CONSUMER RIGHTS IN THE ECUADORIAN LEGAL ORDER", aims to describe through a legal analysis, doctrine and science the various administrative, judicial and extrajudicial mechanisms that protect consumer rights. For the study of the problem the descriptive, analytical and inductive method was applied; for being an investigation to end in the area of the sciences of the right, it assumes a qualitative approach since it fulfills a systematic procedure, that they entail to determine characteristics and qualities of the problem; for the complexity and reached objectives, it is an investigation of non experimental design, of bibliographical, basic, descriptive documentary type, the population involved was constituted by 50 consumers, authorities and directors in charge of guaranteeing the rights of the consumer; for the compilation of information a questionnaire was applied. The results obtained allow us to establish that there is an important set of norms and institutions, dedicated to the protection of the consumer, however, they are used in an irregular way, foundation that allows me to conclude indicating that, our citizens experience generalized ignorance, by a denigrating socialization of the right of consumption.